Constraint representation of 2-dimensional models with respect to avoiding cycles. Issue 1 (2nd January 2017) - Rosendahl, Manfred
ABSTRACT: A geometric constraint system which models 2-dimensional geometries in a form that often no multidimensional equation systems are necessary, when solving a given constraint system, is described. This is achieved because not only constraints between points are used, but also circles and lines are introduced as objects. GRAPHICAL ABSTRACT: